2017
DOI: 10.3390/met7020063
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Toxicity Evaluation of Dextran-Coated Iron Oxide Nanoparticles

Abstract: Abstract:We report the synthesis of dextran-coated iron oxide magnetic nanoparticles (DIO-NPs) with spherical shape and uniform size distribution as well as their accumulation and toxic effects on Jurkat cells up to 72 h. The characterization of dextran-coated maghemite nanoparticles was done by X-ray diffraction and dynamic light scattering analyses, transmission electron microscopy imaging, attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy, magnetic hysteresis, and relaxometry m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…An important criterion that must be taken into account is the stability of synthesized SPIO-NPs in biological fluids with their physiological pH. To solve this issue, SPIO-NPs must be coated with the biocompatible surfactants, which not only prevent SPIO-NPs from agglomeration, but also increase their biocompatibility [ 29 ]. Dextran-coated SPIO-NPs also have higher cellular uptake [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important criterion that must be taken into account is the stability of synthesized SPIO-NPs in biological fluids with their physiological pH. To solve this issue, SPIO-NPs must be coated with the biocompatible surfactants, which not only prevent SPIO-NPs from agglomeration, but also increase their biocompatibility [ 29 ]. Dextran-coated SPIO-NPs also have higher cellular uptake [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…To solve this issue, SPIO-NPs must be coated with the biocompatible surfactants, which not only prevent SPIO-NPs from agglomeration, but also increase their biocompatibility [ 29 ]. Dextran-coated SPIO-NPs also have higher cellular uptake [ 29 ]. During MTT assay for in vitro cytotoxicity, the amount of formazan produced due to mitochondrial activity is directly proportional to the number of living or viable cells, as detected by a spectrophotometer with light absorption [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…de Oliveira et al 2017showed how the addition of dextran to iron-oxide NPs increased biocompatibility in zebrafish larvae; in particular, the treatment with dextran-coated NPs did not determine any significant mortality or changes in the hatching rate of the larvae. The toxicity of dextran modified ironoxide NPs was also investigated by Balas et al (2017) on Jurkat cells. The authors observed low toxicity and small effects on membrane integrity up to 72 h of incubation.…”
Section: Biocompatibility and Immune Escapementioning
confidence: 99%
“…Furthermore, unlike conventional pesticide delivery, the use of nanocarrier can enhance the efficacy and protect the pesticide which is beneficial especially when pesticide with short-lifetime is to be used. 20 Diverse materials such as metal oxides, [21][22][23] SiO2, [24][25][26][27][28] graphene derivatives, [29][30][31] polymers, [32][33][34][35] polysaccharides, [36][37][38] nanocomposites, 39 etc. have been cast-off for the controlled release of pesticides.…”
Section: Introductionmentioning
confidence: 99%